KORELASI HIGIENE DAN SANITASI LINGKUNGAN TERHADAP INFEKSI PROTOZOA USUS PADA ANAK BALITA - As-Syifa, Gina; Anhar, Citra Amanah; Foekh, Neiny Prisy; Inderiati, Dewi (Poltekkes Kemenkes Bandung, 2025)
Intestinal protozoa infections are medical problems closely related to environmental hygiene and sanitation, which are sources of infection. This study aims to analyze the correlation between hygiene, environmental sanitation, and intestinal protozoan infections in toddlers residing in the Bantargebang TPST area of Bekasi City. The study is an observational analytical cross-sectional study conducted from March to May 2024 with 50 infant respondents accompanied by their parents, using purposive sampling. Data were collected from observations, interviews, and examinations of intestinal protozoan infections in fecal samples using the direct method. Data analysis was performed using the chi-squared test. The examination results showed that 28% were positive for intestinal protozoan infections, 44% had poor personal hygiene, and 48% had poor environmental sanitation. The Chi-Square test results indicated that there was no significant correlation between hygiene and intestinal protozoan infection in infants (P = 0.243) and no significant correlation between environmental sanitation and intestinal protozoan infection in infants (P = 0.420). The researchers concluded that there was no significant correlation between hygiene and environmental sanitation and intestinal protozoan infections experienced by toddlers around the Bantargebang TPST in Bekasi City. The researchers suggested finding research locations with high prevalence and researching other factors that may influence intestinal protozoan infections.